Analisis Dana Bantuan Program Keluarga Harapan Untuk Meningkatkan Kesejahteraan Ekonomi Di Kota Bandar Lampung - Ovaliani Anna Sasmita; Erike Anggraeni; Syamsul Hilal (Universitas Batanghari, 2023)
Poverty has made millions of people unable to get a quality education, difficulties in financing health care, lack of savings and no investment, lack of access to public services, lack of employment opportunities, lack of social security and protection for families, increased migration flows to cities, and more severe, poverty causes millions of people to meet their limited needs for food, clothing and boards. Social welfare problems that are currently developing indicate that there are citizens whose rights to their basic needs have not been properly fulfilled because they have not received social services from the state. Thus, social welfare development, as well as development in general, cannot be carried out by the government alone. The purpose of this research is to find out whether the Family Hope Program assistance fund can improve people's welfare in Bandar Lampung. The method used in this research is to use qualitative methods. Based on the results of the study, it was found that the assistance from the Family Hope Program had not been comprehensive and the level of poverty in Bandar Lampung City was not yet complete.